Strength and endurance differences between elite and junior elite ice hockey players. The importance of allometric scaling - Hoff, J.; Kemi, O. J.; Helgerud, J. (International Journal of Sports Medicine, 2005)
The aim of this study was to investigate differences in strength and endurance between elite and elite junior ice hockey players. Participants included 18 elite players and 21 junior elite male players (24.2 ± 4.7 vs. 17.6 ± 0.9 years of age, 84.2 ± 8.1 vs. 72.3 ± 6.0 kg body mass (p < 0.01), 179.9 ± 6.1 vs. 179.0 ± 7.0 cm). Absolute maximal oxygen uptake was significantly higher in elite than junior players (4.8 vs. 4.2 L · min-1, p < 0.01), but relative expressions, including allometric scaling, eliminated the difference. Elite players lifted significantly more weight than juniors in 1 repetition maximum squats (200.0 ± 28.9 vs. 140.3 ± 19.5 kg, p < 0.01) and in bench press (100.8 ± 12.8 vs. 75.3 ± 12.8 kg, p < 0.01). Elite players also ran significantly faster in the 10 m sprint (1.80 ± 0.07 vs. 1.88 ± 0.08 s, p < 0.01), and had greater jumping height (27.2 ± 3.2 vs. 20.5 ± 3.0 cm, p < 0.01) and peak force (2336.4 ± 219.9 vs. 2011.9 ± 180.1 N, p < 0.01) when holding 50 extra kg. No differences were found for the 40 m sprint or for the rate of force development in jumping. This study revealed that the main differences between elite and junior ice hockey players at a high performance level seem to be in strength and body mass. The results therefore identify important factors for juniors to improve in the transition phase from junior to elite level.